“Private and Prestigious” Does Not Necessarily Equal Perfect Fit - Hoffman, Jaimie; Garcia, Julissa (Allies for Education, 2017)
Selecting the right university can be a very nerve-racking experience for students, parents, and families. Let’s face it - without even adding in any other variables, this is a significant financial and time commitment, and for us, as first-generation college students, the confusion and weight is compounded because no one paved the way for us. On top of this, society infiltrates us with the message that the absolute best universities are the “private, elite.” In this letter, we attempt to demystify the difference between public and private universities, share the general characteristics of each, and then discuss the most important factor in selecting the right university – fit. While we will reference some research, we also share this information from our own experiences attending and working at both public and private universities.